The state of knowledge concerning the relationship to knowing in teacher training - Santos, Marquise Meneses; Nascimento, Marilene Batista da Cruz; Guedes, Josevânia Teixeira (Multi-Science Journal, 2020)
This state of knowledge research aims to map the scientific production on the relationship to knowing in teacher training in Brazil, as well as categorize the multiple approaches and perspectives of publications on this theme. Data has been collected from the following academic databases: CAPES (a Brazilian federal government agency that stands for Coordination for the Improvement of Higher Education Personnel), Scopus, SciELO and REPERES (Network of Research on the Relationship to Knowing). This study has originated from skimming titles and abstracts of articles, dissertations and theses whose data have been processed in the light of discursive textual analysis, which involves a cycle of operations that deconstruct a corpus so as to categorize the analysis units. At the end of this stage, the following categories have emerged: school learning, school experience, knowledges (in the plural form) and formative processes. The results disclose the relevance of teachers in the pursuit of a career path with inquisitive attitudes that valorize the Other through a humanistic, dialogic and knowledge-sharing perspective. There is an emergence of Professors/Researchers who reconstruct knowledge, and therefore providing meaning to different knowledges, regardless if these are curricular, disciplinary, professional or experiential. All in all, it has been concluded that the relationship to knowing in teacher training leads to accounting not only for existing difficulties in the process of “learning to learn”, but also for the teacher’s role as mediator between knowledges, the world, his Self and the Other.